2019
DOI: 10.1038/s41598-019-55698-3
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale invasion genetics of the quarantine pest, Anoplophora glabripennis, reconstructed in single outbreaks

Abstract: The xylophagous cerambycid Anoplophora glabripennis, the Asian long-horned beetle (ALB), is highly polyphagous and can colonize a wide range of broadleaved host trees causing significant economic damage. For this reason, it is considered a quarantine pest in Europe and North America. Although the global spread of ALB has been depicted recently, no comprehensive studies exist on the genetic pattern of populations’ establishment and dynamics at fine-scale (i.e. within invasive outbreaks), before eradication meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…hitch-hiking) at a small spatial scale were observed in some regions as in Corsica and in Switzerland (Javal et al 2019a,b;Tsykun et al 2019). Bridgehead events may have contributed to the worldwide spread of ALB (Javal et al 2019). This appears to be the case for the French population in Gien that may have resulted from a bridgehead population from North America (Javal et al 2019a,b) rather than Asia as suggested in previous publications (Cocquempot et al 2003).…”
Section: Albmentioning
confidence: 99%
See 2 more Smart Citations
“…hitch-hiking) at a small spatial scale were observed in some regions as in Corsica and in Switzerland (Javal et al 2019a,b;Tsykun et al 2019). Bridgehead events may have contributed to the worldwide spread of ALB (Javal et al 2019). This appears to be the case for the French population in Gien that may have resulted from a bridgehead population from North America (Javal et al 2019a,b) rather than Asia as suggested in previous publications (Cocquempot et al 2003).…”
Section: Albmentioning
confidence: 99%
“…The resulting genetic differentiation among European establishments may indicate limited gene flow between populations once established, mostly due to the poor dispersal behaviour of this species. A fine-scale study in Switzerland (Tsykun et al 2019) showed that only one or a maximum of two genetic clusters were found within a given tree, suggesting that most ALB individuals remain in proximity to the tree from which they emerged when suitable host trees are available (Smith et al 2001 and2004;Javal et al 2019a,b). Low levels of genetic diversity, high levels of inbreeding, small numbers of founders and large differences in the severity of bottlenecks encountered by introduced populations have shaped the genetic structure of invasive populations (Javal et al 2019a,b).…”
Section: Albmentioning
confidence: 99%
See 1 more Smart Citation
“…Dodds and Orwig 2011), whereas many researchers have focused on the ecology of Anoplophora spp. from the viewpoints of dispersal behavior (Bancroft and Smith 2005; Favaro et al 2015; Hull-Sanders et al 2017; Smith et al 2004; Williams et al 2004), host preference (Faccoli and Favaro 2016; Fujiwara-Tsujii et al 2016; Yasui and Fujiwara-Tsujii 2013) and invasion process (Javal et al 2019a,b; Tsykun et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the relationship between landscape and some longhorn beetles has been described, most studies used microsatellite or mitochondrial DNA markers to study the invasion history and the influence of environmental factors such as climate and altitude (David, Giffard, Piou, Roques, & Jactel, 2016;Haran, Roques, Barnard, Robinet, & Roux, 2015;Javal et al, 2017;Javal et al, 2019;Koutroumpa, Rougon, Bertheau, Lieutier, & Roux, 2013;Tsykun et al, 2019). However, because of the limited number of polymorphic sites and the lack of detailed information on tree species, the dispersal behavior and the genetic model of M. alternatus at a fine scale has not been studied.…”
Section: Introductionmentioning
confidence: 99%